Analisis Uang, Bank dan Kebijakan Moneter - Ustad Adil; Yadi Janwari; Sofian Al-Hakim (IQTISHOD: Jurnal Pemikiran dan Hukum Ekonomi Syariah, 2025)
This research aims to analyze the concepts of money, banking and monetary policy from an Islamic perspective, which is based on the principles of justice and the prohibition of usury. The main focus is how the Islamic financial system contributes to economic stability. The research method used is a qualitative approach by reviewing literature or sources related to the research. The results of this research show that an Islamic monetary system that is free of usury and speculation has the potential to create more sustainable economic stability, as well as the role of Islamic banks in supporting fair monetary policy. These results indicate that Islamic monetary policy is capable of contributing to global financial stability if it is effectively integrated into the modern economic system, although implementation challenges remain.